MEMBANGUN ILMU-ILMU SOSIAL PROFETIK PERSPEKTIF KUNTOWIJOYO - Syahrul Nizar Saragih (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This paper discusses Kuntowijoyo's thoughts on